THE ROLE OF INDEPENDENT STATE INSTITUTIONS IN THE STATE SYSTEM: AN ANALYSIS OF ACCOUNTABILITY AND LIMITS OF AUTHORITY - Syukur, Iskandar (Journal of Scientech Research and Development, 2026)
The development of independent state institutions indicates a shift in the state structure, which no longer relies entirely on the classical division of powers. The existence of these institutions creates a functional institutional relationship with the branches of state power, but also raises issues related to accountability and the clarity of the boundaries of authority. This lack of clarity has the potential to give rise to overlapping authority, inter-institutional conflict, and an imbalance in the distribution of state power. This study aims to analyze the institutional position of independent state institutions and examine accountability and the boundaries of authority within the state system. This research uses a qualitative approach utilizing various relevant literature sources. The results indicate that the accountability practices of independent state institutions are still not uniform and tend to be administrative in nature without in-depth evaluation. The unclear boundaries of authority increase the potential for conflict and reduce the effectiveness of state administration. Strengthening regulations, inter-institutional coordination, and oversight mechanisms are crucial steps to maintain the balance of power and improve the quality of state administration.